Association Between Serum Creatinine Concentrations and Overall Survival in Patients With Colorectal Cancer: A Multi-Center Cohort Study - Yang, Ming; Zhang, Qi; Ruan, Guo-Tian; Tang, Meng; Zhang, Xi; Song, Meng-Meng; Zhang, Xiao-Wei; Zhang, Kang-Ping; Ge, Yi-Zhong; Shi, Han-Ping (Frontiers in Oncology, 2021)
Background Colorectal cancer (CRC) is one of the most common malignancies throughout the world, with high rates of morbidity and mortality. Previous studies reported that serum creatinine (Scr) concentrations were associated with overall survival (OS) in cancer patients, but little is known about the association between Scr and OS in patients with CRC. This study investigated the relationship between Scr concentrations and OS in patients with CRC and examined possible effect modifiers. Methods A retrospective cohort, including 1,733 patients with CRC, was established from a multi-center clinical study. Patients were divided into low (<71 μmol/L in men or <59 μmol/L in women), normal (71-104 μmol/L in men or 59-85 μmol/L in women) and high (>104 μmol/L in men or >85 μmol/L in women) Scr groups. Cox regression analysis was used to examine association between Scr concentrations and OS. Stratified (subgroup) analyses were used to examine men and women separately. Interaction tests were used to evaluate associations between each variable and OS, as well as possible interactions of these variables with Scr levels. Cross-classified analyses were used only in men. Results Patients with low [hazard ratio (HR) = 1.43, 95% confidence interval (CI) = 1.19-1.72; P < 0.001] or high (HR = 1.89, 95% CI = 1.36-2.63; P < 0.001) Scr level had a significantly lower OS than patients with normal Scr levels. Significant interactions with Scr concentrations were observed for body mass index (P for interaction = 0.019) in men. Conclusion Low or high Scr concentration is associated with significantly lower OS in patients with CRC. Future study is warranted to investigate the underlying mechanism.